Development of an isolation procedure and MC-ICP-MS measurement protocol for the study of stable isotope ratio variations of nickel1. Issue 7 (24th July 2015) - Chernonozhkin, Stepan M.; Goderis, Steven; Lobo, Lara; Claeys, Philippe; Vanhaecke, Frank
<x xml:space="preserve">Abstract</x> A method for high-precision analysis of mass-dependent natural variations in Ni isotope ratios, suitable for applications in the planetary sciences, has been developed and evaluated.